2013
DOI: 10.11118/actaun201361030729
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of Ostrich's eggshell at compression

Abstract: NEDOMOVÁ ŠÁRKA, BUCHAR JAROSLAV, STRNKOVÁ JANA: Mechanical behaviour of Ostrich's eggshell at compression. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 3, pp. 729-734 The deformation and fracture behaviour of Ostrich's eggs at the static compression has been investigated. The mechanical properties of egg to compression were determined in terms of average rupture force, specifi c deformation and rupture energy along X and Z axes. Exact description of the eggshell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…60-280.30 N mm -1 , depending on applied direction. Similar values were observed in Lohmann chicken eggs (124.64-133.02 N mm -1 ) by Altuntas & Sekeroglu (2008) and Hisex Brown chicken eggs (158.59-269.90 N mm -1 ) by Nedomova et al (2009), but much higher values were observed for ostrich eggs (932.50-1484.10 N mm 1 ) by Nedomova et al (2013). , respectively.…”
Section: Some Physical Morphological and Mechanical Characteristicssupporting
confidence: 81%
See 1 more Smart Citation
“…60-280.30 N mm -1 , depending on applied direction. Similar values were observed in Lohmann chicken eggs (124.64-133.02 N mm -1 ) by Altuntas & Sekeroglu (2008) and Hisex Brown chicken eggs (158.59-269.90 N mm -1 ) by Nedomova et al (2009), but much higher values were observed for ostrich eggs (932.50-1484.10 N mm 1 ) by Nedomova et al (2013). , respectively.…”
Section: Some Physical Morphological and Mechanical Characteristicssupporting
confidence: 81%
“…Nedomova et al (2014) also reported higher breaking strength in goose eggs (63.80-101.92 N) loaded at the same compression speed of 0.33 mm s -1 as in the present study. On the other hand, much higher breaking strengths are obtained in large eggs, such as ostrich eggs 531.52-904.54 N (Nedomova et al, 2013), whereas small eggs, such as those of Japanese quails (weighing 10.58-14.25 g) have much lower breaking strength, of 6.2-11.4 N (Polat et al, 2007). These results demonstrate the strong influence of egg weight on egg breaking strength.…”
Section: Some Physical Morphological and Mechanical Characteristicsmentioning
confidence: 80%
“…An average Young's modulus of 6.6 GPa was found for ostrich eggs, which is in high contradiction with the 100 GPa value obtained by Nedomová et al [26]. Nonetheless, the reported force -displacement curves for point load tests on ostrich eggs [26] were input into equation (3.7) and give a value of 6.5 GPa, which is remarkably close to the modulus calculated herein.…”
Section: Elastic Properties Of Avian Eggshellssupporting
confidence: 48%
“…During the calcification they excretion in shells 2 to 3 g daily (Bar, 2009). The primary function of the shell is to protect the egg contents from external mechanical influences and microorganisms, which can affect the resulting quality and soundness of the eggs, or the hatchability of reproductive eggs (Nedomová et al, 2013). Shell quality is very important for eggs producers.…”
Section: Introductionmentioning
confidence: 99%